Surprise: An Emotion? (Contributions to Phenomenology, In Cooperation with The Center for Advanced Research in Phenomenology,, 2018)
This volume offers perspectives on the theme of surprise crossing philosophical, phenomenological, scientific, psycho-physiology, psychiatric, and linguistic boundaries. The main question it examines is whether surprise is an emotion. It uses two main theoretical frameworks to do so: psychology, in which surprise is commonly considered a primary emotion, and philosophy, in which surprise is related to passions as opposed to reason. The book explores whether these views on surprise are satisfying or sufficient. It looks at the extent to which surprise is also a cognitive phenomenon and primitively embedded in language, and the way in which surprise is connected to personhood, the interpersonal, and moral emotions. Many philosophers of different traditions, a number of experimental studies conducted over the last decades, recent works in linguistics, and ancestral wisdom testimonies refer to surprise as a crucial experience of both rupture and openness in bodily and inner life. However, surprise is a theme that has not been dealt with directly and systematically in philosophy, in the sciences, in linguistics, or in spiritual traditions. This volume accomplishes just that.